A framework for conflict resolution in multi-agent systems - Basheer G.S.; Ahmad M.S.; Tang A.Y.C. (2023)
In this paper, we analyze the effects of agents' confidence in conflict resolution of a multi-agent system and propose a resolution technique to possible conflicts in the environment. It establishes a framework on agents' confidence and conflict strength and shows the possible limits of agents which provide uncertain information. This paper offers a confidence model that depends on some factors, which suggest that agents' opinions do not have equal confidence level. We exploit such circumstance in selecting appropriate strategy to resolve conflicts between agents. Consequently, we propose a multi-agent framework which examines agents' confidence using specific factors and exploiting the level of confidence for detecting the best strategy to conflict resolution. Springer-Verlag 2013.